Prediction of low cardiac output syndrome in patients following cardiac surgery using machine learning - Hong, Liang; Xu, Huan; Ge, Chonglin; Tao, Hong; Shen, Xiao; Song, Xiaochun; Guan, Donghai; Zhang, Cui (Frontiers in Medicine, 2022)
Background: This study aimed to develop machine learning models to predict Low Cardiac Output Syndrome (LCOS) in patients following cardiac surgery using machine learning algorithms. Methods: The clinical data of cardiac surgery patients in Nanjing First Hospital between June 2019 and November 2020 were retrospectively extracted from the electronic medical records. Six conventional machine learning algorithms, including logistic regression, support vector machine, decision tree, random forest, extreme gradient boosting and light gradient boosting machine, were employed to construct the LCOS predictive models with all predictive features (full models) and selected predictive features (reduced models). The discrimination of these models was evaluated by the area under the receiver operating characteristic curve (AUC) and the calibration of the models was assessed by the calibration curve. Shapley Additive explanation (SHAP) and Local Interpretable Model-Agnostic Explanations (LIME) were used to interpret the predictive models. Results: Data from 1585 patients (982 (62.0%) were male, aged 18 to 88, 212 (13.4%) with LCOS) were employed to train and validate the LCOS models. Among the full models, the RF model (AUC:0.909, 95% CI: 0.875-0.943; Sensitivity:0.849, 95% CI:0.724-0.933; Specificity: 0.835, 95% CI: 0.796-0.869) and the XGB model (AUC:0.897, 95% CI: 0.859-0.935; Sensitivity:0.830, 95% CI: 0.702-0.919; Specificity: 0.809, 95% CI: 0.768-0.845) exhibited well predictive power for LCOS. Eleven predictive features including left ventricular ejection fraction (LVEF), first post-operative blood lactate (Lac), left ventricular diastolic diameter (LVDd), cumulative time of mean artery blood pressure (MABP) lower than 65mmHg (MABP <65 time), hypertension history, platelets level (PLT), age, blood creatinine (Cr), total area under curve above threshold central venous pressure (CVP) 12 mmHg and 16 mmHg, and blood loss during operation were used to build the reduced models. Among the reduced models, RF model (AUC:0.895, 95% CI: 0.857-0.933; Sensitivity:0.830, 95% CI: 0.702-0.919; Specificity: 0.806, 95% CI: 0.765-0.843) revealed the best performance. SHAP and LIME plot showed that LVEF, Lac, LVDd and MABP <65 time significantly contributed to the prediction model. Conclusions: In this study, we successfully developed several machine learning models to predict LCOS after surgery, which may avail to risk stratification, early detection and management of LCOS after cardiac surgery.